Endothelin and aneurysmal subarachnoid haemorrhage: a study of subarachnoid cisternal cerebrospinal fluid. - Gaetani, P (1994)
Endothelin (ET) is considered one of the most potent vasoconstrictor polypeptides; several experimental studies have suggested its possible role in the pathogenesis of arterial vasospasm after subarachnoid haemorrhage (SAH). Previously reported data on plasma and CSF levels of endothelin in patients with a diagnosis of SAH have been controversial. Cisternal endothelin CSF levels and the possibility that they could be related to vasospasm and other clinical patterns of SAH were investigated. CSF samples were obtained from 55 patients admitted after angiographic diagnosis of intracranial aneurysm. Levels of ET-1 and ET-3 were measured through radio-immunoassay technique. Twelve patients who had operations for unruptured aneurysms were considered control cases; 43 patients with SAH were classified according to: Hunt and Hess grading at admission, vasospasm grading, CT classification and timing of surgery. In all 55 patients ET-1 was measured, while positive levels of ET-3 were found only in 17 cases of 48. No linear correlation was found between cisternal CSF ET-1 levels when considering time of surgery, CT classification, Hunt and Hess grading at admission, and vasospasm grading. The results of ET-3 assay should be considered with great caution because of the low percentage of positive cases. Cisternal CSF levels of ET-1 and ET-3 are not directly related to the occurrence of arterial vasospasm after the aneurysm rupture, or to other major clinical patterns of SAH; however, ET-1 expression occurs either in paraphysiological (unruptured aneurysm) or in pathological conditions (SAH). It is suggested that ET may potentiate, or may be potentiated by, other factors playing a consistent pathophysiological role in the development of vasospasm.